Bilingual experience and intrinsic functional connectivity in adults, aging, and Alzheimer's disease. Issue 1 (26th July 2021) - Jafari, Zahra; Perani, Daniela; Kolb, Bryan E.; Mohajerani, Majid H.
Abstract: The past decade marked the beginning of the use of resting‐state functional connectivity (RSFC) imaging in bilingualism studies. This paper intends to review the latest evidence of changes in RSFC in language and cognitive control networks in bilinguals during adulthood, aging, and early Alzheimer's disease, which can add to our understanding of brain functional reshaping in the context of second language (L2) acquisition. Because of high variability in bilingual experience, recent studies mostly focus on the role of the main aspects of bilingual experience (age of acquisition (AoA), language proficiency, and language usage) on intrinsic functional connectivity (FC). Existing evidence accounts for stronger FC in simultaneous rather than sequential bilinguals in language and control networks, and the modulation of the AoA impact by language proficiency and usage. Studies on older bilingual adults show stronger FC in language and frontoparietal networks and preserved FC in posterior brain regions, which can protect the brain against cognitive decline and neurodegenerative processes. Altered RSFC in language and control networks subsequent to L2 training programs also is associated with improved global cognition in older adults. This review ends with a brief discussion of potential confounding factors in bilingualism research and conclusions and suggestions for future research.